What goes up must come down? 25 years of public trust in the police - Bradford, Ben (International journal of police science & management, 2024)
Public trust in the police is an almost ever-present feature of United Kingdom policy, political and indeed cultural debates, and this has been true right across the past quarter century. Concentrating on the population-level picture, and on England and Wales, in this article I outline what we know about changes in ‘trust and confidence’ over the past two decades or so, and make comparison with changes in other, closely associated, indicators. Why it might be that over this period trust in police first increased significantly, and then declined? Answers to this question implicate what might be termed the political economy of trust. Change in public trust may be due to a whole set of factors operating across multiple levels of policing and the society in which it takes place.